Effect of Exposure to Socio-Political Violence and Abuse During Childhood on Executive Planning in Adult Life - Montoya-Arenas, David Andrés; Londoño-Guzmán, Daniel; Franco, José G.; Gaviria, Ana M. (Frontiers in Psychiatry, 2022)
Objective. The exposure to unfavorable environments during childhood negatively affects the development of the executive planning abilities in the adult life. In countries with socio-political conflicts, children are exposed to traumatic events as a result of child abuse and socio-political violence. The purpose of this study was to analyze the effect of the exposure to both forms of adverse childhood experiences on the executive planning abilities in adults from the general population. Method. The history of child abuse and socio-political violence during childhood was assessed, as well as the executive planning abilities, in 59 adults older than 49 without cognitive impairment or depressive disorder. Results. 88.1% experienced at least one child abuse event and 47.5% was exposed to socio-political violence. Sexual abuse and physical abuse (child abuse) were associated with reduced performance in executive planning. Forced displacement and extortion (socio-political violence) had a mixed relationship with the planning ability, improving some aspects and worsening some others. Kidnapping was associated with increased capacity and control of the working memory and executive planning. Conclusions. The traumatic events during childhood have differential effects on the executive planning skills in the adult life. The exposure to sexual and physical abuse negatively affects executive skills, on the other hand, socio-political violence has a mixed or positive impact. Specifically, kidnapping favors the executive planning processes, probably under an evolutionary adaptive mechanism.